Creating a Decentralized Integrated Performance Index Water Supply System: An Examination of SiPAS in the Brantas River Basin - Andawayanti, Ussy; Asmaranto, Runi; Sajali, M. Amar; Suhartanto, Ery; Hidayat, Mustafa Mukti; Utami, Rizki Tri (Engineering, Technology & Applied Science Research, 2026)
Access to clean water is a critical issue, particularly in rural and remote areas where conventional water supply systems are inadequate. This study develops an integrated Performance Index Model (PIM) to evaluate the Simple Water Supply System (SiPAS) in the Brantas river basin, East Java, Indonesia, incorporating technical, managerial, and social factors. Existing models primarily emphasize technical aspects, neglecting the crucial roles of social dynamics and governance. Thirty-one SiPAS sites were evaluated using the Structural Equation Modeling (SEM) and Partial Least Squares (PLS) techniques. The results show that technical factors, such as infrastructure quality, account for 72.1% of performance variation, underlining the importance of robust infrastructure. Managerial and social aspects, although smaller in magnitude (26.7% and 15.1%, respectively), are also vital for system sustainability, highlighting the importance of local government and stakeholder involvement. An Android application for real-time data collection and monitoring was developed, supporting decision-making for system improvement and long-term sustainability.